Hegel's hidden history of the Fall - Demjaha, D (2020)
This thesis argues that Hegel’s claim that the coming of Christ is the central axis of history, entails a twofold punctuation of history by the Christ-Event. As Benedetto Croce recognised, Christianity inaugurates for Hegel a ‘new’ history, which he called the ‘history of Truth’. I argue that this history of Truth is preceded, on the other side of the Christ-Event, by a hidden, ‘history of the Fall’. I identify this ‘history of the Fall’ with Hegel’s developmental narrative of religious history, which plots the movement from Naturreligion to the emergence of Christianity. The ‘history of the Fall’ is, accordingly, the history of the emergence of revelation from the immediacy of natural life. For Hegel, this life is historically ‘lapsarian’, having emerged with the breakdown of the Zweck of history into sin and slavery. The Jewish (and later Christian) religion represents this historical catastrophe as a ‘Fall’ of Adam, whom Hegel reads typologically as Christ. The Christ-Event is therefore both the goal and the starting point of history. It is the goal of the ‘history of the Fall’, and the starting point of the ‘history of Truth’, whose ‘first man’ is Christ, the second Adam. However, while this ‘history of Truth’ coincides with Christianity as ‘revelation’, the ‘history of the Fall’ is ‘hidden’ from the merely ‘natural consciousness’ of Naturreligion, just as sin is, for Christian theology, known only under grace. The emergence of the Genesis Fall narrative is therefore linked by Hegel to the possibility of understanding history because it is necessary for the possibility of human self-understanding (as unfree and, therefore, as not yet Geist). The development of consciousness leading up to the Christ-Event, which I refer to as the ‘history of the Fall’, designates the concretisation of its self-understanding as ‘fallen’, from the ‘pictorial’ form of the Genesis narrative as ‘story’, to the revelation of human ‘fallenness’ in polemical antithesis to the life and teaching of Christ as ‘history’. In this way, I argue that the Christ-Event constitutes humanity as a historical ‘unity’ in its rejection of the offer for the kingdom, and therefore constitutes the historical past as a ‘history of the Fall’. I argue that highlighting the role of the Fall narrative in this way, allows us to understand Hegel’s philosophy of history as formulating a developmental narrative of the origins of human life as emerging from historical failure, without giving up on its essence as a Christian Heilsgeschichte (as is common with secularising readers, from Hyppolite and Kojève, to Žižek).